Studi Ketercukupan Kapasitas Saluran Jalan Pada Jalan Dengan Kelandaian Cukup Tinggi (Studi Kasus Jalan Kawah Ijen, Bondowoso) - Noor Salim (Media Ilmiah Teknik Sipil, 2021)
Stagnant water in the highway area is the cause of disruption of the smooth flow of vehicle traffic. Even the overflowing of air from the road creates a large flood supply in the road area. The problem of flooding in the Ijen Bondowoso crater road area was also triggered by the inability of the channel that functions to fill the flood water discharge that occurs in this road area. From this problem, it is necessary to study regarding the adequacy of the capacity of the road channel on roads with a fairly high slope such as what happened in the area of Ijen Crater road, Bondowoso From the results of this study it can be seen that the average daily rainfall is the result of 100,461 mm and the relative average rainfall intensity of each channel for the 10 year return period is 63,301 mm / hour. The flood discharge plan is calculated from 2 to 100 years. In this drainage design analysis, the design flood discharge is calculated for only 10 years, and a planned flood discharge is obtained of 0.423 m3 / second. The channel required to fill the flood discharge is a rectangular channel with the size B = H = 0.6 m. It is recommended to always carry out a comprehensive study with regard to changes in the road body of the road along with the increase in existing traffic. As well as the infrastructure of the existing channel and feeding the community around the road, it will be clean and not littering, especially in the road channel